The Creation and Configuration of Asian Girlhood: An Examination of Sharon Tran’s Asian Girlhood in the Shadows of U.S. Empire / Sharon N. Tran’s Asian Girlhood in the Shadows of U.S. Empire - Kim, Jung (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
This review examines Sharon N. Tran’s Asian Girlhood in the Shadows of U.S. Empire (University of Minnesota Press, 2026), which analyzes the construction of Asian girlhood through the intersecting forces of race, gender, and empire. Drawing on literary analysis and historical texts, Tran explores Japanese American incarceration, Korean War camp towns, Operation Babylift, and the Vietnam War to reveal how Asian girls are simultaneously rendered disposable and idealized as human capital. While Tran’s book has been praised as a significant contribution to girlhood and Asian American studies, the review notes gaps in South Asian representation, limited methodological transparency, and an epilogue that offers limited practical direction.